Strategy for Small-medium Scale Contractor Performance Improvement in ASEAN Competitive Market. (2017) - Handayani, Fajar Sri
Abstract: In facing current pressing sustainable issues and ASEAN Economic Community (AEC) where construction sector is on so-called 'free competition', national private construction industry players, i.e. consulting firms and contractors, must enhance their performance in order to improve their service, compete, and gain advantage. These players must apply the concept of strategic management in which environmental analysis and strategic alternative decision stage is involved. This study identifies the prevailing problems encountered by the Indonesian contractors firms. The case study focused on and collected data from small to medium contractors in Central Java. Data were analyzed and strategic decisions were formulated based on current baseline. The appropriate strategic alternatives for small contractor were market development by maintaining clients' trust, improving the human resources through certification, and implementing effective and efficient construction methods which minimize waste. For medium contractors, the attractive market development can be attained by optimizing the role of enterprise organizations, building teamwork, improving the control system, applying sustainable construction via efficient construction method.